Sustainability Leadership Compass: Navigating the Digital–Green Transition - Lindéus, Gustav; Shetty, Santosh (Global journal of Business and Integral Security, 2026)
We developed and tested a new tool called the Sustainability Leadership Compass (SLC) to measure how well public companies integrate sustainability and digital technology into their leadership and governance practices. The SLC looks at 10 key indicators across four areas: Vision, Governance, Digital Integration, and External Validation. Using evidence directly cited from annual reports, companies receive a score from 0-10 that reflects what typical investors can easily find and verify. We tested the tool on 41 companies across Europe, North America, and Asia, spanning major industries. Our findings revealed a clear group of sustainability leaders, with European companies generally scoring highest. While we saw some industry patterns, these were less definitive in this initial study. For business leaders and practitioners, the SLC highlights common success factors like board oversight of ESG issues, sustainability-linked executive pay, third-party verification, and visible digital tools like dashboards and AI that drive results